Submerged membrane – (GAC) adsorption hybrid system in reverse osmosis concentrate treatment - Sukanyah, S.; Nguyen, T.V.; Jeong, S.; Kandasamy, J. (ELSEVIER, 2015)
Wastewater reclamation plants using reverse osmosis as the final polishing treatment produce reverse osmosis concentrate (ROC), which consists of high salinity, nutrients and (recalcitrant) organics. The ROC collected from the water reclamation plant in Sydney was treated with a micro filtration (MF)–GAC hybrid system that removed natural and synthetic organics prior to its discharge into the environment. The MF–GAC hybrid system’s performance was studied in terms of trans-membrane pressure (TMP) development, and organics removal. These features were measured using liquid chromatography–organic carbon detection (LC–OCD), Fluorescence Excitation-Emission matrix (F-EEM), and Liquid chromatography with tandem mass spectroscopy (LC–MS). Adding GAC into the membrane reactor reduced the TMP by reducing membrane fouling both through mechanical scouring and pre-adsorption of organics. F-EEM confirms the removal of humics-like and fulvic-like compounds by GAC from ROC. Pharmaceuticals and personal care products (PPCPs) were also removed by the MF–GAC hybrid system.
Keywords: Reverse osmosis concentrate; Organics; GAC; Hybrid system